To study the effect of capacitor, resistor and pre-scalar unit towards frequency counter / Gabreal Johnny Gabil - Gabil, Gabreal Johnny (2013)
The modern electronic frequency counter is a versatile device. In its simplest mode, it provides a method to determine the frequency of any suitable signal applied to its input port. The accuracy of the measurement is directly relate to the internal resolution of the counter and the accuracy of its internal time base (quartz crystal oscillator). The frequency counter operates on the principle of the input frequency into the counter for a predetermined time however, a simple techniques for low frequency measurement is not available. In this project, the research design a frequency counter which have surpass the capability of the supposed PIC16F628A with several tweaks towards the device to increase the counter reading.